The illness experience of HIV-infected low-income Coloured mothers in the Winelands region : theoretical and practical implications - Herbst, Elsa (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (Psychology))—University of Stellenbosch, 2006.